463 Effect of maternal overnutrition on insulin signaling in foal skeletal muscle. (7th December 2018) - Bradbery, A; Coverdale, J; Hammer, C; Wickersham, T; Dunlap, K; Leatherwood, J; Satterfield, M
Abstract: Evidence suggests that late-gestation maternal overnutrition predisposes foals to metabolic disease. Our objective was to determine the effects of maternal overnutrition on insulin signaling in foal skeletal muscle. Sixteen Quarter Horse mares were used in a completely randomized design, and maintained on pasture at a body condition score 6 until the start of third trimester. On d 235 gestation, mares were stratified by BW, BCS, and expected foaling date, and randomly assigned to receive one of two dietary treatments where diets were formulated to meet dietary requirements during late gestation (CON; n=8), and an overfed group (HIGH; n=8) where mares received an additional 40% above CON. Five h after parturition, foals were euthanized, and the gluteus medius, triceps brachii, and semitendinosus were harvested for analyses. G lucose transporter 4 ( GLUT4 ) and insulin receptor isoform A ( IR-A ) mRNA levels were determined by qPCR. Western immunoblotting was used to quantify insulin receptor β (IRβ ), GLUT4, extracellular signal-regulated protein kinases 1/2 (ERK1/2), protein kinase B (Akt), c-Jun N-terminal kinase (JNK), and their phosphorylated forms with tubulin as the loading control. All data were analyzed using PROC MIXED of SAS. Ratios of phospho to total ERK1/2 and JNK were greater (P<0.05) in foal gluteus medius from HIGH mares compared to CON. There were no differences observed for phospho to total protein ratios in semitendinosus and triceps brachii muscles; however total ERK1/2 tended to be elevated (P<0.10) in semitendinosus from foals of CON mares compared to HIGH. There were no differences in gene expression or protein concentrations of GLUT4, IR-A, IRβ, or Akt ( P >0.10) irrespective of maternal diet or muscle type. These data identify muscle specific changes in the downstream insulin receptor signaling cascade, which may contribute to future metabolic abnormalities in response to maternal overnutrition.